Prospects for Fishery‐Induced Collapse of Invasive Asian Carp in the Illinois River. Issue 10 (18th October 2013) - Tsehaye, Iyob; Catalano, Matthew; Sass, Greg; Glover, David; Roth, Brian
ABSTRACT: Invasive Asian Carp are threatening to enter Lake Michigan through the Chicago Area Waterway System, with potentially serious consequences for Great Lakes food webs. Alongside efforts to keep these fishes from entering Lake Michigan with electric barriers, the state of Illinois initiated a fishing program aimed at reducing their densities through intensive commercial exploitation on the Illinois River. In this study, we explore prospects for the "collapse" of Asian Carp in the Illinois River through intensive fishing. Based on a meta‐analysis of demographic data, we developed a dynamic simulation model to compare the performance of existing and alternative removal strategies for the Illinois River. Our model projections suggest that Asian Carp in the Illinois River are unlikely to collapse if existing harvest rates are kept below 0.7 or fishing continues to be size selective (targeting only fish >500 mm or <500 mm) or species selective (targeting mostly Bighead Carp), although their biomasses could be greatly reduced. We argue that it would still be possible to achieve fishing effort targets predicted by our model to collapse the Asian Carp populations if efforts to expand commercial fishing are combined with economic incentives to improve size selectivity and species targeting.